Patient satisfaction and experience with various modes of Xylocaine administration for cervical dilatation and endometrial curettage: a randomized interventional study - Kanchan, Swati; Hebbar, Shripad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Patient satisfaction after a surgical procedure is an important outcome of hospital care. Many of the gynaecological menstrual problems such as abnormal uterine bleeding, postmenopausal bleeding requires endometrial evaluation which is done traditionally by dilatation and curettage. But this procedure is painful and requires appropriate pain management protocol. The aim is to evaluate the post-operative patient satisfaction following dilatation and curettage procedure. Methods: This study was conducted in a tertiary care hospital belonging to a medical college. A total of 236 patients were recruited for the study who subsequently underwent dilatation and curettage with different mode of Xylocaine anesthesia for pain relief. Of them 16 patients were excluded due to valid reasons and the remaining 220 were interviewed face to face following the procedure. The level of anxiety was assessed using Beck’s Anxiety inventory and also perception of satisfaction was documented along with complication related to the anesthesia. Results: The overall level of satisfaction was higher in the group receiving both paracervical block and intrauterine instillation of lidocaine during the procedure of dilatation and curettage. A further analysis showed that increase in level of satisfaction was due to improvement in pain scores due to combined mode of paracervical and endometrial anesthesia. Conclusions: A multimodal pain management protocol which involves pre-procedural sedation, combined cervical and endometrial anesthesia improves overall outcome with respect to reduction in anxiety scores and postoperative satisfaction levels.